Tectonics, Climate, and Landscape Evolution 2006
DOI: 10.1130/2006.2398(23)
|View full text |Cite
|
Sign up to set email alerts
|

Tectonically driven exhumation of a young orogen: An example from the southern Apennines, Italy

Abstract: In many young orogens of the Mediterranean region, Quaternary tectonics and regional uplift are traditionally considered strictly correlated, but few data are actually available for precise calculations of uplift rates. Such quantitative studies are needed to define the relationships between local faulting and large-scale uplift, and to formulate correct hypotheses on the geodynamic scenario in which the regional raising occurred. In addition, data about burial depths of sediments or tectonic loadings suffered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 23 publications
4
55
0
Order By: Relevance
“…Starting from the middle Pleistocene, another relevant uplift event occurred (D'Argenio et al, 1986;Brancaccio et al, 1991;Schiattarella et al, 2003). During the late Pleistocene the chain was characterized by stability of the Tyrrhenian belt and uplift of the axial zone of the chain, foredeep basin and foreland area (Cosentino and Gliozzi, 1988;Westaway, 1993;Bordoni and Valensise, 1998;Schiattarella et al, 2003Schiattarella et al, , 2006.…”
Section: Geological and Geomorphological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting from the middle Pleistocene, another relevant uplift event occurred (D'Argenio et al, 1986;Brancaccio et al, 1991;Schiattarella et al, 2003). During the late Pleistocene the chain was characterized by stability of the Tyrrhenian belt and uplift of the axial zone of the chain, foredeep basin and foreland area (Cosentino and Gliozzi, 1988;Westaway, 1993;Bordoni and Valensise, 1998;Schiattarella et al, 2003Schiattarella et al, , 2006.…”
Section: Geological and Geomorphological Settingmentioning
confidence: 99%
“…The usefulness of palaeosurfaces as a geomorphological signature of uplift in the southern Italian Apennines has been a hot issue for geomorphologists, geophysicists and geologists in the last decade (Amato and Cinque, 1999;Basili et al, 1999;Schiattarella et al, 2003Schiattarella et al, , 2006Ascione et al, 2003;Amato et al, 2003). The recognition of areas with different tectonic activity could be useful to define a relationship between local faulting and large-scale uplift.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors identified two main uplift stages in the Early Pleistocene, and another relevant event was marked by uplift that occurred in the Middle Pleistocene (D'Argenio et al 1986;Brancaccio et al 1991;Schiattarella et al 2003). Finally, in the Late Pleistocene the chain was characterized by stability of the Tyrrhenian belt and uplift of the axial zone of the chain, the foredeep basin, and the foreland area (Westaway 1993;Bordoni & Valensise 1998;Schiattarella et al 2003Schiattarella et al , 2006.…”
Section: Geological and Geomorphological Features Of The Study Areamentioning
confidence: 99%
“…4) -kaolinite is only observed in correlated levels within the Galestri Formation, where it exhibits a high crystallinity, and is totally absent in analogously correlated levels within the Scisti Silicei Formation (Di Leo et al 2002;Schiattarella et al 2003Schiattarella et al , 2006) -suggest that a more intense weathering period has also contributed to the formation of these weathered horizons and that a change to climate conditions typical of a mainly warm/humid climate occurred (Fig. 9).…”
Section: Paleoclimate Implicationsmentioning
confidence: 99%
“…Brancaccio et al 1988;Bosi et al 1996;Amato & Cinque 1999;Basili et al 1999;Coltorti & Pieruccini 2000;Bartolini et al 2003, D'Alessandro et al 2003Boenzi et al 2004;Gioia & Schiattarella 2006;Schiattarella et al 2006). These paleosurfaces represent the remnants of gentlyrolling ancient landscapes, generated by fluvio-denudational processes, which are preserved at different altitudes above the local base levels of erosion.…”
Section: New Morphostratigraphic and Chronological Constraints For Thmentioning
confidence: 99%